PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DENGAN KEPRIBADIAN PROAKTIF SEBAGAI PEMODERASI DAN KOMITMEN AFEKTIF SEBAGAI PEMEDIASI (Studi pada Karyawan KSP Bhina Raharja di Kabupaten Pemalang) - Wisnu Pradana, Aditya; Andriyani, Andriyani (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to analyze the effect of transformational leadership style on employee performance with proactive personality as moderator and affective commitment as mediator. This study consists of two dependent variables, one independent variable, one moderating variable and one mediating variable. The dependent variables in this study are task performance and contextual performance. The independent variable in this study is a transformational leadership style. The moderating variable in this study is proactive personality and the mediating variable in this study is affective commitment. The population in this study were all employees of the Bhina Raharja savings and loan cooperative in Pemalang Regency. The sample used purposive sampling, amounting to 120 respondents. The data collection technique is done by using a questionnaire. Analysis of research data using SEM (Structural Equation Modeling) analysis which is operated through the WARP PLS 5.0 program. The results of this study indicate that transformational leadership style on task performance and contextual performance has a positive and significant effect and affective commitment has a positive and significant effect on contextual performance. Proactive personality as a moderating variable weakens the relationship between transformational leadership style and task performance. Affective commitment as a mediating variable can strengthen the relationship between transformational leadership styles and contextual performance